Mutation in TDRD9 causes non-obstructive azoospermia in infertile men. Issue 9 (23rd May 2017) - Arafat, Maram; Har-Vardi, Iris; Harlev, Avi; Levitas, Eliahu; Zeadna, Atif; Abofoul-Azab, Maram; Dyomin, Victor; Sheffield, Val C; Lunenfeld, Eitan; Huleihel, Mahmoud; Parvari, Ruti
Abstract : Background: Azoospermia is diagnosed when sperm cells are completely absent in the ejaculate even after centrifugation. It is identified in approximately 1% of all men and in 10%–20% of infertile males. Non-obstructive azoospermia (NOA) is characterised by the absence of sperm due to either a Sertoli cell-only pattern, maturation arrest, hypospermatogenesis or mixed patterns. NOA is a severe form of male infertility, with limited treatment options and low fertility success rates. In the majority of patients, the cause for NOA is not known and mutations in only a few genes were shown to be causative. Aim: We investigated the cause of maturation arrest in five azoospermic infertile men of a large consanguineous Bedouin family. Methods and results: Using whole genome genotyping and exome sequencing we identified a 4 bp deletion frameshift mutation in TDRD9 as the causative mutation with a Lod Score of 3.42. We demonstrate that the mutation results in a frameshift as well as exon skipping. Immunofluorescent staining with anti-TDRD9 antibody directed towards the N terminus demonstrated the presence of the protein in testicular biopsies of patients with an intracellular distribution comparable to a control biopsy. The mutation does not cause female infertility. Conclusion: This is the first report of a recessive deleterious mutation in TDRD9 in humans. The clinical phenotype recapitulates that observed in the Tdrd9 knockout mice where this gene was demonstrated to participate in long interspersed element-1 retrotransposon silencing. If this function is preserved in human, our data underscore the importance of maintaining DNA stability in the human male germ line.